Stable isotopes in monitoring terrestrial arthropods - Komonen, Atte; Torniainen, Jyrki; Kiljunen, Mikko (Frontiers in Ecology and Evolution, 2022)
Monitoring of arthropods focuses typically on changes in population and range size over time. Yet, there are a myriad of other aspects that could and should be monitored under the ongoing global and local environmental change. Stable isotope analysis, widely employed in short-term ecological studies, has potential in long-term monitoring of arthropods. Here we discuss the use of stable isotopes in monitoring terrestrial arthropods, provide some empirical examples of the use of bulk tissue samples in stable isotope analysis, and outline future directions in using compound-specific stable isotope analysis in monitoring. We performed a literature search for 2012–2021 to see if stable isotopes have been specifically used in monitoring of terrestrial arthropods. The literature shows that stable isotopes have been successfully used to reveal ecological phenomena (dispersal, trophic interactions, resource use) that would have been difficult or impossible to detect by other means. Yet, stable isotopes have been underused in arthropod monitoring programs, but the growing number of basic studies on stable isotope ecology and methodology provides crucial basis needed for developing monitoring programs. Stable isotopes provide technically, economically and ecologically feasible addition to the traditional monitoring methods of terrestrial arthropods.